2013
DOI: 10.1038/nature12650
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated growth in the absence of DNA replication origins

Abstract: DNA replication initiates at defined sites called origins, which serve as binding sites for initiator proteins that recruit the replicative machinery. Origins differ in number and structure across the three domains of life1 and their properties determine the dynamics of chromosome replication. Bacteria and some archaea replicate from single origins, whilst most archaea and all eukaryotes replicate using multiple origins. Initiation mechanisms that rely on homologous recombination operate in some viruses. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
201
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(218 citation statements)
references
References 38 publications
(69 reference statements)
13
201
1
1
Order By: Relevance
“…In contrast, the S. elongatus dnaA disruptant not only exhibited normal growth, but also displayed increasing cell viability in long culturing conditions. Interestingly, polyploid archaea tolerate the deletion of all replication origins and mutants exhibit a faster growth rate compared with WT counterparts (Hawkins et al, 2013). Freshwater cyanobacteria are also polyploid and their chromosomes are replicated asynchronously; that is, they may not initiate replication only once per chromosome per cell cycle (Chen et al, 2012;Jain et al, 2012;Watanabe et al, 2012) DnaA-independent replication control and facilitated DnaA-independent growth under various environmental conditions in freshwater cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the S. elongatus dnaA disruptant not only exhibited normal growth, but also displayed increasing cell viability in long culturing conditions. Interestingly, polyploid archaea tolerate the deletion of all replication origins and mutants exhibit a faster growth rate compared with WT counterparts (Hawkins et al, 2013). Freshwater cyanobacteria are also polyploid and their chromosomes are replicated asynchronously; that is, they may not initiate replication only once per chromosome per cell cycle (Chen et al, 2012;Jain et al, 2012;Watanabe et al, 2012) DnaA-independent replication control and facilitated DnaA-independent growth under various environmental conditions in freshwater cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Later marker frequency studies using next-generation sequencing identified additional replication origins [15,18]. Hawkins and colleagues have shown that H. volcanii strain H26, currently used in our laboratory, carries up to four replication origins on the main chromosome [15]. They also revealed a very striking feature of H. volcanii cells: this species is viable even after removal of the all identified replication origins [15].…”
mentioning
confidence: 91%
“…Two of these replication origins were first described by genetic and physical mapping by Norais and colleagues [30]. Later marker frequency studies using next-generation sequencing identified additional replication origins [15,18]. Hawkins and colleagues have shown that H. volcanii strain H26, currently used in our laboratory, carries up to four replication origins on the main chromosome [15].…”
mentioning
confidence: 97%
“…It will also be important to study the initiation process in species with single and multiple origins and the coordination between initiations at different origins. Recently it was shown that Haloferax volcanii can survive without a canonical origin (Hawkins et al, 2013). Further work is needed to show how initiation occurs in those cells, and to determine if Perspective on archaeal DNA replication this is halophile-specific or a more widespread phenomenon.…”
Section: The Futurementioning
confidence: 99%